English in Kerala: Plus a change? - P. Bhaskaran Nayar (TESL-EJ 12.3, December 2008, 2008)
This article overviews the status, ecology, use, and the teaching/learning of English in the southern Indian state of Kerala. It does so along two overlapping dimensions. A socio-demographic dimension situates the ecology of English in Kerala in the generalIndian context, and relates it to the ethno-linguistic identity of Kerala. A second applied linguistic dimension tries to explore some of the distinctive features of English taught and used in Kerala, and comments on the prevailing institutionalised praxis of the teaching and learning of English in schools and colleges, leading on to some educational, functional, social and communicational implications intra- and internationally